A cross-sectional study of factors associated with carotid atherosclerosis - Dai, Guokui; Cai, Xiangsheng; Ye, Chuanjiang; Zhang, Yuzhen; Guan, Ruoping (Frontiers in Physiology, 2024)
Objective The aim of this work was to study the relationship between carotid atherosclerosis (CAS) and several indexes and provide a basis for the prevention and treatment of cardiovascular and cerebrovascular diseases. Methods There were 11,028 adults who underwent physical examination at the Guangzhou Cadre and Talent Health Management Center from January 2023 to December 2023 and were selected as research subjects. Retrospective analysis was used to understand the carotid atherosclerosis of the examined population and analyze its relationship with sex, age, blood pressure, blood glucose, blood lipids, renal function, 25-hydroxyvitamin D, neutrophil to lymphocyte count ratio (NLR), platelet to lymphocyte count ratio (PLR), systemic immune inflammation index (SII), monocyte count to high-density lipoprotein cholesterol ratio (MHR), triglyceride glucose body mass index (TyG-BMI), insulin resistance metabolic index (METS-IR), and other indicators. Results Among 11,028 subjects, the detection rate of carotid atherosclerotic thickening (CAT) was 12.00% and carotid atherosclerotic plaque (CAP) was 25.11%. The CAT and CAP detection rates in men were 13.32% and 28.78%, respectively, which were higher than the CAT detection rate of 8.28% and CAP detection rate of 14.80% in women, and the differences were statistically significant (both p < 0.001). Multivariate logistic regression analysis using TyG-BMI and METS-IR as two indicators was modeled separately, and the results showed that CAS was associated with men, increasing age, and systolic blood pressure. The area under the curve (AUC) was analyzed using the subject’s work characteristic (ROC) curve in the descending order of METS-IR, TyG-BMI, and MHR. The combination of the three indexes of sex, age, and METS-IR predicted atherosclerosis with the highest AUC values. Conclusion Carotid atherosclerosis is highly prevalent in men. Elevation of systolic blood pressure, fasting glucose, MHR, and TyG-BMI (or METS-IR) with age are independent influences on carotid atherosclerosis. The three indexes of MHR, TyG-BMI, and METS-IR, respectively, in combination with sex and age, can be used as a new and effective index to predict CAS.